Holy representations in European religious duties (1200- 1600) (Al-Academy, 2016)
The representations of the Holy in Christian painting Art represents a penalty of eternal relationship between any human society and sacred representations and forms that he belives in what is characterized by its clear tendency to knowledge and aclear focus on the spiritual experience that make up the human relationship with holy spirit and essence. Search has ment to study the forms of its presence in the art work of the middle ages.Research involved four shapters .first chapter includes research problem which centered around the following question;what is holy ? whats its represetations in Christian painting? And the importance and need of the study .and the goal of research and definitaions of the terms of research.Second chapter consists tow sections .and the indications that resulted from it.and previous studies first section titled the concept of sacred in the religios and philosophical thought.secound section titled sacred representaions in Christian painting.Third chapter determined research community .and research sample that was chosen deliberately,and consisted five models,wich was analised to give resujts of research ;1-there was many types of sacred such as (god ) and (human) and (vegetarian )and (symbolic)and abstract meanings like (wisdom,justice,and law )The researcher mentioned conclusions.and some recommendations,and proposals and index of research sources.Tags//representation,sacred,Christianart,holy,middle ages painting